Case Report: Anlotinib combined with PD-1 inhibitor and sequential GA regimen or FOLFIRINOX Chemotherapy in treatment of KRAS G12V mutated pancreatic ductal adenocarcinoma with liver metastasis: A case and literature review - Wang, Yunpeng; Wang, Bofang; Xiang, Lin; Deng, Junge; Xu, Bo; He, Puyi; Pu, Weigao; Wang, Haiyun; Fan, Yong; Chen, Hao (Frontiers in Immunology, 2022)
There is a high mortality rate associated with pancreatic cancer, and the incidence has been rising globally in recent decades. When patients are diagnosed, there is little chance that surgery will be beneficial. Systemic chemotherapy is the currently accepted treatment option for patients with metastatic advanced pancreatic cancer. However, a very limited survival improvement is possible with chemotherapy for advanced pancreatic cancer, and chemotherapy resistance plays a significant role in poor prognosis. Despite the fact that targeting growth factor receptor inhibitors such as anti-VEGFR antibodies significantly improves survival in pancreatic cancer, only a very small number of patients benefit from the treatment. As emerging drugs, immune checkpoint inhibitors (ICIs) have demonstrated significant therapeutic effects in several tumor types, but monotherapy is not effective in pancreatic cancer. In the first-line treatment of solid tumors, combination therapy may result in remarkable outcomes. Here in, we have reported a younger patient with pancreatic ductal adenocarcinoma with liver metastasis (PDACLM) who had a long-term partial response and good tolerance in the combination of anlotinib and PD-1 inhibitor and chemotherapy. Gene analysis suggested only one mutation in the KRAS G12V gene. Consequently，there is some hope for patients with pancreatic cancer, especially for KRAS G12V gene mutated patient. Upon reviewing the literature, this patient's combination therapy is the first to have been reported.